Nipa Forest as the Ecological Services in Eastern Coast of Thailand - PIEKKOONTOD, Tantus; PACHANA, Pumiphat K.; HRIMPENG, Karnjana; CHAROENJIT, Kitsanai (Journal of Environmental Management and Tourism; Vol 11 No 7 (2020): JEMT Volume XI Issue 7(47) Winter 2020, 2020)
The objectives aimed to revision the current situation of the Nipa forest area according to land use as well as the direct and indirect value of use from Nipa palm in the Eastern-Coastal Watershed. From the study, the Nipa forest area in the East-Coast Gulf of Rayong, Chanthaburi, and Trat have a total area of 0.295 km 2 , which covers the basin of Chanthaburi, Prasae, Trat, and Welu Sub-watershed. Interview and group discussion have been collected from 398 households. The result confirms that 53% of total household income is generated from nipa forest productivity such as fishes, crabs and prawn, whereas aquacultural and non-farm incomes were originating to 28% and 19% of total income, respectively. The result succeeds that revenue from the Nipa forest as fish, crab, prawn and nipa product is 36%, 28%, 9% and 27%, respectively. Therefore, the results established that local source of revenue generally relies on the Nipa forest ecosystem . Nypa fruticans (Nipa palm) are significant sources of subsistence to people who living in riparian and coastal zone in the eastern coast basin of Thailand. Local peoples have traditionally managed the Nipa palm service for the sources of food and construction materials. The result show that Income from the gathering of nipa was the foremost income source (53.8 %) as the raw material to make the products. The most important of nipa utilization, 36 % were made of nipa roof, 28% were made of tobacco wrap, 22% of houses were made of dessert and wrapped it by nipa leaves. Only Nipa palm product was 2,425.72 U.S. dollar/year (equal to 75,786 bath/year) Fisheries value from the Nipa forest, fish were the main product (358.48 U.S. dollar/year) which followed by shrimp that the value was 336.08 U.S. dollar/year and the average income from fisheries was 1,009.2 U.S. dollar/year. Therefore, results approved that local source of revenue generally related on the Nipa forest ecosystem. Local people thought that, nipa area have been decreased. (88%) due to the disturbance of Nipa forest. the majority cause of degradation due to capitalist exploitation. Most of respondent (74%) were surveillance and notification to the local government to conservation Nipa forest and the management of Nipa forest resources could be take the awareness to their family (68%). Increased nipa area in the village or community forest (22%) and access to the schedule to collect the natural product from Nipa forest (7%), the respondents are willing to participate in determining the time to harvest Nipa product and require the government to support, promote, and provide training to produce products from Nipa Palm.